Reimagining the United States organ procurement and transplant network - Perakslis, Eric; McCourt, Brian; Knechtle, Stuart (Frontiers in Transplantation, 2023)
The United States system of solid organ transplantation is overseen by the Organ Procurement Transplantation Network (OPTN). Recent announcements from the Health Resources and Services Administration (HRSA) indicate their clear intention to reform the system . We agree with the original intention of the National Organ Transplant Act (NOTA) to require one entity to oversee transplantation to integrate policy with the complex realities of organ procurement and transplantation practice. A contemporary business platform model best captures the appropriate structure for coordinating organ transplantation, as the seamless exchange of organs between related groups is the essential function to facilitate. A business platform framework that includes public and private, academic and industry partners can best accomplish the important goal of equitable and efficient organ transplantation.